2017
DOI: 10.1038/srep43441
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-27 Enhances the Potential of Reactive Oxygen Species Generation from Monocyte-derived Macrophages and Dendritic cells by Induction of p47phox

Abstract: Interleukin (IL)-27, a member of the IL-12 cytokine family, plays an important and diverse role in the function of the immune system. We have previously demonstrated that IL-27 is an anti-viral cytokine which inhibits HIV-1, HIV-2, Influenza virus and herpes simplex virus infection, and enhances the potential of reactive oxygen species (ROS) generating activity during differentiation of monocytes to macrophages. In this study, we further investigated the mechanism of the enhanced potential for ROS generation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…S8 ). Given that, miR-SX4 was first detected in IL-27 treated macrophages 31 and we have previously reported that IL-27 exerts anti-HIV effects in Monocyte Derived Macrophages (MDM) 29 , 30 , 66 , CD4+T cells 67 and mature DCs 68 . Therefore, there is also a potential that miR-SX4 may functionally exert anti-HIV effects in these primary target cells of HIV virus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S8 ). Given that, miR-SX4 was first detected in IL-27 treated macrophages 31 and we have previously reported that IL-27 exerts anti-HIV effects in Monocyte Derived Macrophages (MDM) 29 , 30 , 66 , CD4+T cells 67 and mature DCs 68 . Therefore, there is also a potential that miR-SX4 may functionally exert anti-HIV effects in these primary target cells of HIV virus.…”
Section: Discussionmentioning
confidence: 99%
“…The protein concentration was determined using the bicinchoninic acid (BCA) protein assay kit (Thermo Fisher Scientific). Using a total of 20 μg protein, western blot analysis was performed as previously described 66 . Antibody binding was visualized using ECL Prime Western Detection Reagent (GE-Healthcare) and LAS-4000 (Fujifilm, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Whole-cell lysate proteins (100 μg) were subjected to 2D-PAGE analysis as described [30]. After separation by 2D-PAGE, the samples were transferred to a membrane for western blot analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Oxidative stress, as a concept formulated in 1985, is induced when ROS generation is increased, or ROS scavengers are dysregulated [ 77 ]. Since oxidative stress is strongly correlated with inflammation and cell death [ 74 , 78 , 79 ], the imbalance of ROS generation and scavenging systems is an alarming signal for cellular metabolisms. In addition, mitochondrial ROS convey information to the nucleus and modulate the expression of nuclear genes accordingly in both physiological [ 80 ] and pathological states [ 66 ].…”
Section: Ros Serve As the New Sensing Network For Homeostasis And Strmentioning
confidence: 99%